Stakeholders' views on maternity care shortcomings in rural Ghana: An ethnographic study among women, providers, public, and quasiprivate policy sector actors. (6th April 2017) - Ayanore, Martin Amogre; Pavlova, Milena; Biesma, Regien; Groot, Wim
Summary: Access to skilled provider and emergency obstetric care is not universal across all districts in Ghana. The lived experiences of 3 stakeholder groups on maternity care shortcomings in 3 rural Ghanaian districts are examined in this study. We applied an ethnographic study approach where field data were collected between March to May 2015 in 3 rural districts of northern Ghana. Data were collected among women with recent births experiences (n = 90), health care providers (n = 16), and policy actors (n = 6). Transcripts were read through to identify similar and divergent stakeholders' views. Significant expressions and experiences of stakeholders on maternity care shortcomings were extracted and evaluated to define key themes. Four themes emerged: social/community factors, payments for health care, facility level factors, and policy level factors. The results show that traditional women's roles divest time for maternity care. Poor transport arrangements, insufficient health workforce, health funding gaps, insurance reimbursements delays, and catastrophic health expenditures on travel and drugs are attested as major barriers across all stakeholder groups in all districts studied. The discussion of the study findings suggests it is important to ascertain the scale of informal payments and their impacts on health access. Investments in health workforce and reliable ambulatory service systems could help address poor referral difficulties in rural areas of the country. Social support for community initiatives that pool funds could provide extra resources and relieve cost access‐related challenges for using maternity care in rural settings in Ghana.